"I am a free human being with an independent will": uma análise da tradução da personagem Jane Eyre da literatura para o cinema - Pereira, Giselle Andrade (2021)
This dissertation aims to analyze the adaptation process of the novel Jane Eyre, first published in 1847, written by the English writer Charlotte Brontë, to the homonymous films in 1944 and 2011, directed respectively by Robert Stevenson and Cary Joji Fukunaga. In the analysis we observed reading traits as the language system changed, focusing on the translation process of the character Jane Eyre to the screen. In the novel, Charlotte Brontë criticizes nineteenth-century English society by inscribing a character that questions the social role of women and gender stereotypes of the time, thus creating an alternative image of what was expected of women in the Victorian Era. As the film adaptations create new images of the novel and the characters, we wondered what aspects of the main character the films studied here created and what strategies were used in the adaptation process. To this purpose, we based our study on the theoretical contribution of Gaskell (1997), Gilbert & Gubar (2000), Showalter (1993), Ingham (2008) and Woolf (2013; 2014), who discuss Victorian literature written by women and Charlotte Brontë’s work; as well as the texts of Bordwell (2005), Lefevere (2007), Stam (2008) and Hutcheon (2013), who discuss translation as rewriting, intertext, film adaptation and narration in film. The general results of the analysis show that, when translated into film by Stevenson, the character Jane Eyre is transformed into the feminine ideal of the 1940s, in which the questions and reflections, as well as the rejection of the passivity made by the character of the novel are erased, giving way to a passive character who has her voice diminished, much of the film, by the character Rochester. Fukunaga’s film adaptation, on the other hand, produced at the beginning of the 21st century, creates the image of Jane Eyre as the protagonist and with a voice that emphasizes herself, and it is given more space for her psychological construction. We consider that those changes made by the directors and producers of the films were influenced by the ideologies and poetics of their respective times.